Intratumor heterogeneity is biomarker specific and challenges the association with heterogeneity in multimodal functional imaging in head and neck squamous cell carcinoma. Issue 139 (June 2021) - Rasmussen, Jacob H.; Olin, Anders B.; Lelkaitis, Giedrius; Hansen, Adam E.; Andersen, Flemming L.; Johannesen, Helle H.; Kjaer, Andreas; Fischer, Barbara M.; Specht, Lena; Bentzen, Søren M.; von Buchwald, Christian; Wessel, Irene; et al.
Highlights: Intra-tumoral heterogeneity in the cancer-related immunohistochemical (IHC) biomarkers investigated here was considerable. Tumor heterogeneity is biomarker specific. IHC-assessed heterogeneity showed weak associations with variability in the functional imaging biomarkers. Heterogeneity is related to biology in a more complex manner than can be explained simply by tumor size. Abstract: Rationale: Tumor biopsy cannot detect heterogeneity and an association between heterogeneity in functional imaging and molecular biology will have an impact on both diagnostics and treatment possibilities. Purpose: Multiparametric imaging can provide 3D information on functional aspects of a tumor and may be suitable for predicting intratumor heterogeneity. Here, we investigate the correlation between intratumor heterogeneity assessed with multiparametric imaging and multiple-biopsy immunohistochemistry. Methods: In this prospective study, patients with primary or recurrent head and neck squamous cell carcinoma (HNSCC) underwent PET/MRI scanning prior to surgery. Tumors were removed en bloc and six core biopsies were used for immunohistochemical (IHC) staining with a predefined list of biomarkers: p40, p53, EGFR, Ki-67, GLUT1, VEGF, Bcl-2, CAIX, PD-L1. Intratumor heterogeneity of each IHC biomarker was quantified by calculating the coefficient of variation (CV) in tumor proportion score among the six core biopsies within each tumor lesion. The heterogeneity in the imaging biomarkers was assessed by calculating CV in 18 F-fluorodeoxyglucose (FDG)-uptake, diffusion and perfusion. Concordance of the two variance measures was quantified using Spearman's rank correlation Results: Twenty-eight patients with a total of 33 lesions were included. There was considerable heterogeneity in most of the IHC biomarkers especially in GLUT1, PD-L1, Ki-67, CAIX and p53, however we only observed a correlation between the heterogeneity in GLUT1 and p53 and between Ki-67 and EGFR. Heterogeneity in FDG uptake and diffusion correlated with heterogeneity in cell density. Conclusion: Considerable heterogeneity of IHC biomarkers was found, however, only few and weak correlations between the studied IHC markers were observed. The studied functional imaging biomarkers showed weak associations with heterogeneity in some of the IHC biomarkers. Thus, biological heterogeneity is not a general tumor characteristic but depends on the specific biomarker or imaging modality.